THE EFFECT OF LEARNING MEDIA AND LEG MUSCLE FLEXIBILITY ON SEPAK SILA LEARNING OUTCOMES IN SEPAK TAKRAW GAMES OF PJKR FIK STUDENTS OF SEMARANG STATE UNIVERSITY (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
This study aims to 1) Found out the different effect of the used of learning media between modificated ball and standard ball of sepak sila outcomes of PJKR FIK UNNES students; 2) To determine the different effect of leg muscle flexibility which is divided into two categories, namely, a) the high flexibility of both leg muscle and the low flexibility of both leg muscle on sepak takraw results of the PJKR FIK UNNES students, 3) to knew the interaction between the use of learning media and the leg muscle flexibility of sepaksila outcomes in sepak takraw games of PJKR FIK UNNES students. The method used in this study was an experimental method with a 2x2 factorial design. The population of this study was semester four students of PJKR FIK UNNES consisting of 160 students and 40 samples taken by using purposive random sampling technique. The division of groups was based on leg muscle flexibility test results with the high category and the low category, then, the students were further divided into two groups: group 1consisting of 20 people with the treatment of using learning media and group 2 consisting of 20 people using the standard media. The study was conducted from the 30th of May to the1st of July in Sport Sciences Faculty, Semarang State University. The research hypotheses testing was by the significant level of 95 percent. Before the Hypotheses test was conducted, the sample normality test using a Bartlet test with significant level of ∂ 0.05 and a variant homogeneity test using lilifors of ∂ 0.05 percent of significant level were done. All data were analyzed by using SPSS for Windows 15.0 version. This reseach concludes 1) that there are diferent effect between sepak sila learning using the medium of modificated ball and using the medium of standard ball on the result of sepak sila in the sepak takraw games of PJKR FIK UNNES students, 2) there is a significant difference between high leg muscle flexibility and lower leg muscle flexibility of the sepak sila learning outcomes in sepak takraw games of PJKR FIK UNNES students. The result of sepak sila of the students with high leg muscle flexibility is better than the students with low leg muscle flexibility. 3) There is interaction between the use of learning media and leg muscle flexibility in the sepak takraw games of the PJKR UNNES FIK students.